Deimplementation in the provision of opioid agonist treatment to achieve equity of care for people engaged in treatment: a qualitative study - Anna Conway; Alison D. Marshall; Sione Crawford; Jeremy Hayllar; Jason Grebely; Carla Treloar (Implementation Science, 2023)
Abstract Background Deimplementation, the removal or reduction of potentially hazardous approaches to care, is key to progressing social equity in health. While the benefits of opioid agonist treatment (OAT) are well-evidenced, wide variability in the provision of treatment attenuates positive outcomes. During the COVID-19 pandemic, OAT services deimplemented aspects of provision which had long been central to treatment in Australia; supervised dosing, urine drug screening, and frequent in-person attendance for review. This analysis explored how providers considered social inequity in health of patients in the deimplementation of restrictive OAT provision during the COVID-19 pandemic. Methods Between August and December 2020, semi-structured interviews were conducted with 29 OAT providers in Australia. Codes relating to the social determinants of client retention in OAT were clustered according to how providers considered deimplementation in relation to social inequities. Normalisation Process Theory was then used to analyse the clusters in relation to how providers understood their work during the COVID-19 pandemic as responding to systemic issues that condition OAT access. Results We explored four overarching themes based on constructs from Normalisation Process Theory: adaptive execution, cognitive participation, normative restructuring, and sustainment. Accounts of adaptive execution demonstrated tensions between providers’ conceptions of equity and patient autonomy. Cognitive participation and normative restructuring were integral to the workability of rapid and drastic changes within the OAT services. Key transformative actors included communities of practice and “thought leaders” who had long supported deimplementation for more humane care. At this early stage of the pandemic, providers had already begun to consider how this period could inform sustainment of deimplementation. When considering a future, post-pandemic period, several providers expressed discomfort at operating with “evidence-enough” and called for narrowly defined types of data on adverse events (e.g. overdose) and expert consensus on takeaway doses. Conclusions The possibilities for achieving social equity in health are limited by the divergent treatment goals of providers and people receiving OAT. Sustained and equitable deimplementation of obtrusive aspects of OAT provision require co-created treatment goals, patient-centred monitoring and evaluation, and access to a supportive community of practice for providers.